2022
DOI: 10.2215/cjn.16421221
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Tacrolimus Variability and Association with De Novo Donor-Specific Antibody Formation in Pediatric Kidney Transplant Recipients

Abstract: Background and objectivesHigh tacrolimus intrapatient variability has been associated with inferior graft outcomes in patients with kidney transplants. We studied baseline patterns of tacrolimus intrapatient variability in pediatric patients with kidney transplants and examined these patterns in relation to C1q-binding de novo donor-specific antibodies.Design, setting, participants, & measurementsAll tacrolimus levels in participants who underwent kidney-only transplantation at a single pediatric center fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Tis retrospective study of 46 kidney transplant recipients demonstrated that patients with high TAC intrapatient variability (coefcient of variation >30%) had a higher risk of de novo donor-specifc antibody formation (hazard ratio, 5.35; 95% confdence interval, 2.45 to 11.68), which was associated with poor graft outcomes [4]. Te Consensus on Modifable Risk Management in Transplantation expert panel also recommended that large fuctuations in TAC levels and high exposure levels in the early posttransplant period should be avoided because they increase mortality caused by events related to excessive immunosuppression such as infections, cardiovascular events, and malignancies [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis retrospective study of 46 kidney transplant recipients demonstrated that patients with high TAC intrapatient variability (coefcient of variation >30%) had a higher risk of de novo donor-specifc antibody formation (hazard ratio, 5.35; 95% confdence interval, 2.45 to 11.68), which was associated with poor graft outcomes [4]. Te Consensus on Modifable Risk Management in Transplantation expert panel also recommended that large fuctuations in TAC levels and high exposure levels in the early posttransplant period should be avoided because they increase mortality caused by events related to excessive immunosuppression such as infections, cardiovascular events, and malignancies [19].…”
Section: Discussionmentioning
confidence: 99%
“…In triple therapy regimens with TAC, mycophenolate mofetil, and glucocorticoid, maintaining TAC C 0 at 8-15 ng/ml is recommended for 0-3 months postsurgery [3]. Intrapatient variability refects fuctuations in trough levels over a specifc time interval [4]. Intrapatient variability of TAC C0 increases the risk of poor prognosis after transplantation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, long‐term graft and patient survival rates are still suboptimal, 7–9 and the lifelong requirement for immunosuppression in children is associated with complications and mortality 10 . Immunosuppression minimization and non‐adherence, that is especially prevalent among pediatric patients, 11 can lead to increased risk of generating de‐novo donor‐specific HLA antibodies (dnDSA) and inferior graft outcomes 12 . Allosensitization, in turn, can cause chronic rejection, which is a leading cause of graft loss 13 .…”
Section: Introductionmentioning
confidence: 99%
“…10 Immunosuppression minimization and non-adherence, that is especially prevalent among pediatric patients, 11 can lead to increased risk of generating de-novo donor-specific HLA antibodies (dnDSA) and inferior graft outcomes. 12 Allosensitization, in turn, can cause chronic rejection, which is a leading cause of graft loss. 13 Lastly, allosensitization after graft loss leads to increased sensitization as measured by degree of calculated panel reactive antibodies (cPRA), reducing access to compatible retransplantation and increasing waiting time at relisting.…”
Section: Introductionmentioning
confidence: 99%
“…However, data are mixed as to the effect of MPA levels and intrapatient variability on DSA formation and donorreactive T lymphocytes (9). The study by Piburn et al (2) was not equipped to evaluate whether corticosteroids modified the effect of tacrolimus on de novo DSA formation, as only patients with a high immunologic risk were prescribed prednisone (2).…”
mentioning
confidence: 99%